Osteoporosis Is Characterized by Altered Expression of Exosomal Long Non-coding RNAs - Teng, Zhaowei; Zhu, Yun; Zhang, Xiguang; Teng, Yirong; Lu, Sheng (Frontiers in Genetics, 2020)
Abstract: Osteoporosis is a metabolic bone disease characterized by a decrease in bone mass and degradation of the bone microstructure, which increases bone fragility and risk of fracture. However, the molecular mechanisms of osteoporosis remain unclear. The current study attempts to elucidate the role of exosomal long noncoding RNA in the pathology of osteoporosis. Peripheral blood was collected from persons with (OP) or without (NC) osteoporosis, and the serum exosomes were extracted using ultra centrifugation process. Total RNA of exosomes was isolated, and the lncRNAs profiling was done using RNA-Seq experiments. In silico analysis resulted in identification of 393 differentially expressed (DE) lncRNAs in OP vs NC, with 296 that were up-regulated and 97 were down-regulated. Bioinformatics analysis of potential target mRNAs of lncRNAs with cis-acting mechanism showed that mRNAs co-located with DE lncRNAs were highly enriched in osteoporosis-related pathways, including regulation of insulin secretion, activation of MAPK activity, cellular response to metal ions, fucosylation and proteolysis. Together these results suggest that lncRNAs of serum exosomes could play a significant role in development of osteoporosis and such information may be helpful in developing diagnostic markers and therapeutic modules for osteoporosis.